Alternatives to ginger root oil aromatherapy for improved mating performance of sterile Ceratitis capitata (Diptera: Tephritidae) males. (13th December 2011) - Juan‐Blasco, M.; San Andrés, V.; Martínez‐Utrillas, M. A.; Argilés, R.; Pla, I.; Urbaneja, A.; Sabater‐Muñoz, B.
Abstract: Autocidal control of the Mediterranean fruit fly Ceratitis capitata (Wiedemann) is an environmentally friendly and safe practice employed successfully worldwide. A key component in the Sterile Insect Technique (SIT) is to release sterile males that can compete with wild males in nature. Exposure of sterile males to ginger root oil (GRO) in the form of aromatherapy prior to release has been shown to significantly improve male competitiveness and performance. However, alternatives to GRO exposure are desired to (i) reduce personnel costs and handling‐time requirements and (ii) find new aromatherapeutic compounds. In this study, alternatives to GRO aromatherapy were investigated, such as incorporating GRO into the post‐teneral diet, or employing other molecules (limonene and linalool) occurring naturally in citrus release areas. Our results reveal that both the GRO‐supplemented diet and linalool aromatherapy were equal to the GRO aromatherapy control in improving mating performance in sterile males. In contrast, exposure to limonene did not afford a mating advantage to sterile mates when compared to the control. In addition, sterile male survival was not affected by any of the treatments tested. Implications for how both new approaches could be implemented in SIT programmes in citrus production areas are discussed.